Ameliorative effects of epigallocatechin-3-gallate nanoparticles on 2,4-dinitrochlorobenzene induced atopic dermatitis: A potential mechanism of inflammation-related necroptosis - Han, Mengguo; Wang, Xue; Wang, Jian; Lang, Dongcen; Xia, Xiaohua; Jia, Yongfang; Chen, Ying (Frontiers in Nutrition, 2022)
Atopic dermatitis (AD) is a common autoimmune and chronic inflammatory cutaneous disease with a relapsing-remitting course. Necroptosis is a regulated necrotic cell death mediated by receptor-interacting protein 1 (RIP1), receptor-interacting protein 3 (RIP3), and mixed lineage kinase domain-like pseudokinase (MLKL), which is activated by tumor necrosis factor-α (TNF-α). However, the mechanism and the role of necroptosis have not been delineated in AD progression. (-)-Epigallocatechin-3-gallate (EGCG), the main biological activity of tea catechin, is well known for its beneficial effects in the treatment of skin diseases. Here, PEG-PLGA-EGCG nanoparticles (EGCG-NPs) were formulated to investigate the bioavailability of EGCG to rescue cellular injury following the inhibition of necroptosis after AD. 2,4-dinitrochlorobenzene (DNCB) was used to establish AD mouse models. As expected, topically applied EGCG-NPs elicited a significant amelioration of AD symptoms in skin lesions, including reductions in the ear and skin thickness, dermatitis score, and scratching behavior, which was accompanied by redox homeostasis restored early in the experiment. In addition, EGCG-NPs significantly decreased the expression of inflammatory cytokines like TNF-α, interferon-γ (IFN-γ), interleukin-4 (IL-4), interleukin-6 (IL-6), and interleukin-17A (IL-17A) in a time-dependent manner than those of in AD group. As a result, the overexpression of RIP1, RIP3, and MLKL in the entire epidermis layers was dramatically blocked by EGCG-NPs, as well as the expression of phosphorylated p38 (p-p38), extracellular signal-regulated kinase 1 (ERK1), and extracellular signal-regulated kinase 2 (ERK2). These findings promote that EGCG-NPs formulation represents a promising drug-delivery strategy for the treatment of AD by maintaining the balance of Th1/Th2 inflammation response and targeting necroptosis.